Serum C - Reactive Protein, White Cell Counts and Neutrophil Percentage are Predictors For Distal Ureteric Calculus Expulsion Rate: A Prospective Study - Shah, Ram Sagar; Sigdel, Kaushal (Journal of Nobel Medical College, 2019)
Background: To determine the relationship between expulsion rate of distal ureteric calculus less than orequal to 10mm in size and C reactive protein (CRP) level, white cell count and neutrophil percentage.Materials and Methods: A total of 186 patients with distal ureteric calculus of ≤10mm were evaluated for stone expulsion rate and its correlation with serum CRP, white cell count and neutrophil percentage. All patients received tablet Tamsulosin 0.4mg for 4 weeks or till the expulsion of stone. Patients were called weekly till 4 weeks, or early if there was history of stone expulsion. Patients were divided in two groups according to normal and elevated CRP levels, white cell count and neutrophil percent age at baseline for statistical analysis.Results: The patients had an average age of 35.6 } 13.9 years. 52.2% were male. Ratio of right to left was1.58:1. Majority of the patients with distal ureteric calculus ≤ 10mm passed their stone (74.7 %) with medical expulsion therapy. Expulsion of stone less than 5mm was statistically significant (p0.017). Patients with normal neutrophil percentage and normal CRP level had higher stone expulsion rate than elevated neutrophil or CRP (85.2% vs. 40.9, 91.8% vs. 30.8% respectively).In patients with normal white cell count, 86.4% passed their stone while in elevated white cellcount group 39.1% passed their stone.Conclusion: This study showed patients with distal ureteric calculus of ≤10mmwith normal CRP level and normal neutrophil count had higher expulsion rate while WBC count showed no statistically significant association.